Legislative Drafting as Anticipatory Legal Interpretation: Minimizing Judicial-Creative Power Through Doctrinal Precision - Akmal, Akmal; Muhlizar (Inovasi Pratama Internasional. Ltd, 2026)
This study examines the efficacy of legislative drafting as a mechanism for anticipatory legal interpretation in Indonesia's constitutional system, specifically analyzing whether doctrinal precision in statutory formulation reduces judicial-creative intervention. Through quantitative analysis of 2,847 judicial review decisions (2003-2024) and 45,891 Supreme Court cassation cases (2018-2025), this research demonstrates an inverse correlation between legislative drafting quality and judicial activism. Constitutional Court data reveals a 17% grant rate for judicial reviews, with 68% of successful challenges attributable to drafting ambiguities, internal inconsistencies, and inadequate normative precision. Supreme Court cassation statistics show 12.98-14.98% reversal rates, predominantly involving statutory interpretation conflicts. The findings indicate that legislation scoring above 75% on the Legislative Clarity Index experiences 73% fewer judicial interventions. This research employs regression analysis to isolate drafting quality as a predictive variable, controlling for political salience and constitutional significance. The study concludes that implementing rigorous doctrinal precision through enhanced academic research methodology, regulatory impact assessment, and systematic harmonization reduces judicial-creative power while strengthening legislative supremacy within Indonesia's separation of powers framework. These results provide empirical foundation for reforming Indonesia's legislative drafting protocols, particularly the Naskah Akademik (academic paper) requirement mandated since 2011, which current analysis reveals insufficient methodological rigor in 64% of examined cases